Magnetic torque obtained using finite element modelling of electromagnetic micro relay / Azahar Taib, Mohamad Adha Mohamad Idin and Nor Azlan Othman - Taib, Azahar; Mohamad Idin, Mohamad Adha; Othman, Nor Azlan (Research Management Institute (RMI), 2012)
Micro Electromechanical Systems (MEMS) is an area of research and applications that is becoming increasingly popular. One of MEMS device that is becoming increasingly important in a wide range of industries such as the computer industry, the medical industry and the automotive industry is micro relay. Generally, there are three types of micro relay based on actuation methods; electrostatic, electrothermal and electromagnetic. This research project focuses on electromagnetic micro relay. The need to study the magnetic behavior of electromagnetic micro relay is due to ongoing demand in area of micro relay design and fabrication. This study will focus on analyzing the magnetic behaviors of a specific electromagnetic micro relay. It involves the analytical and finite element modeling. The results from these two analyses are compared in order to verify the reliability of results obtained. Prior to the validation, a complete model of micro relay is developed using finite element modeling via ANSYS software. Investigations on magnetic behaviors of the electromagnetic micro relay are performed via Finite Element Analyses. By varying the current density on the EM planar coil on the micro relay structure, the operating principle of electromagnetic micro relay can be simulated and observed. In addition, it also includes the investigation of magnetic torque upon the armature of the micro relay when certain parameters are varied. The parameters are the thickness of the armature, air gap between the permanent magnet and EM planar coil, and the amount of current density applied to EM planar coils. The effect of the parameter's variation are presented and discussed. These results provide a good insight of the magnetic behavior of the investigated electromagnetic micro relay which will be very useful in designing an electromagnetic micro relay.